2020
DOI: 10.1186/s40659-020-00279-2
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells-derived MiR-223 destroys intestinal barrier function by inhibition of CLDN8 expression in intestinal epithelial cells

Abstract: Background: Mast cells (MCs) have been found to play a critical role during development of inflammatory bowel disease (IBD) that characterized by dysregulation of inflammation and impaired intestinal barrier function. However, the function of MCs in IBD remains to be fully elucidated. Results: In our study, we used exosomes isolated from human mast cells-1 (HMCs-1) to culture with NCM460, HT-29 or CaCO2 of intestinal epithelial cells (IECs) to investigate the communication between MCs and IECs. We found that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…Mast cells (MCs) can secrete exosomes that display biological functions in RNA and protein transfer, intercellular communication and immunoregulation [127,128]. It was pointed that MC-exosomes have been reported to destroy intestinal barrier function, which is attributed to exosome-carried miRNAs transferred to targeted cells [129]. Recent studies found that MC-derived exosomes can be taken up by lung cancer cells, and subsequently increase cancer cell proliferation by transferring KIT protein [130].…”
Section: Mast Cell-derived Exosomesmentioning
confidence: 99%
“…Mast cells (MCs) can secrete exosomes that display biological functions in RNA and protein transfer, intercellular communication and immunoregulation [127,128]. It was pointed that MC-exosomes have been reported to destroy intestinal barrier function, which is attributed to exosome-carried miRNAs transferred to targeted cells [129]. Recent studies found that MC-derived exosomes can be taken up by lung cancer cells, and subsequently increase cancer cell proliferation by transferring KIT protein [130].…”
Section: Mast Cell-derived Exosomesmentioning
confidence: 99%
“…Mast cells play a critical role in development of IBD. A recent study showed that exosomes from human mast cells are loaded with miR-223, and that delivery of this miRNA into IECs downregulates the expression of the TJ-related proteins ZO-1, occludin, and claudin-8, which in turn elicit the subsequent increase in intestinal permeability that contributes to inflammation and disease development [ 73 ].…”
Section: Intercellular Communication By Evs In Intestinal Homeostamentioning
confidence: 99%
“…It has been reported that miR‐223 is involved in the pathogenesis of IBD by regulating various immune cells and signaling pathways 4‐8 . Furthermore, miR‐223 from human mast cells‐1 (HMCs‐1) inhibits CLDN8 expression to destroy intestinal barrier function in IBD 19 …”
Section: Discussionmentioning
confidence: 99%